Scale-up of microreactor: Effects of hydrodynamic diameter on liquid–liquid flow and mass transfer. (23rd November 2020) - Wang, Xiaoda; Wang, Yongming; Li, Fan; Li, Ling; Ge, Xuehui; Zhang, Shuilu; Qiu, Ting
Highlights: Liquid-liquid flow and mass-transfer were investigated at the characteristic dimensions of 0.8, 1.6 and 3.0 mm for the scale-up of micro-reactor. Decrease of hydrodynamic diameter of T-mixer resulted in the improvement and reduction of volumetric mass transfer coefficients at low and high liquid velocity, respectively. More than 20% mass transfer occurred in T-mixers even at milli-scale. Prediction equations of volumetric mass transfer coefficients, applicable from micro-scale to milli-scale, were provided for the T-mixer and capillary reactor system. Abstract: To examine the scalability of a microreactor to the milli-scale, the liquid–liquid two-phase flow and mass transfer in a capillary reactor system were investigated. The flow pattern gradually transformed from a surface-force-controlled flow into a gravity-force-controlled flow with an increase of hydrodynamic diameter. In the T-mixer, the volumetric mass-transfer coefficient decreased and increased with an increase in the capillary diameter at low and high superficial liquid velocities, respectively. Because of the different mass-transfer mechanisms in the T-mixer and capillary, this scale-up effect became weaker in the capillary reactor system, particularly at a high superficial liquid velocity. A minimum 18% of mass was transferred in the T-mixer even at the milli-scale, suggesting the significant contribution of the T-mixer to mass transfer in the capillary reactor system. Empirical equations for predicting the volumetric mass-transfer coefficient of the T-mixer and the capillary reactor system in the hydrodynamic diameter range of 0.8–3.0 mm were formulated.